The Clinical Trial Outcomes of Med-Zenith PT-Valve in the Treatment of Patients With Severe Pulmonary Regurgitation - Shang, Xiaoke; Dong, Nianguo; Zhang, Changdong; Wang, Yanggan (Frontiers in Cardiovascular Medicine, 2022)
Objective: Nearly 2/3 of patients with dilated right ventricular outflow tract (RVOT) were excluded from pulmonary valves transplantation due to the lack of size-matched valves. Here, we explored the safety and efficacy of the Med-Zenith PT-Valve for the treatment of patients with severe pulmonary regurgitation. Methods: 22 Patients with severe PR (grade 3+,4+) were enrolled based on the anatomical features of native RVOT and the valve design. The immediate, 3-months and 1-year post-procedural follow-up data were analyzed. Results: The baseline mean systolic diameters in the distal main pulmonary artery (MPA), MPA sinus junction, MPA sinus, pulmonary annulus, RVOT aneurysm and muscular outlet measured with computed tomography were 33.6±6.1mm, 34.0±5.8mm, 37.9±6.0mm, 32.4±7.3mm, 41.9±9.3mm and 34.4±8.0mm, respectively. The PT-Valve landing zone was set within these levels. Successful valve implantations were achieved in all patients without noticeable device malposition, coronary artery compression, pulmonary branch obstruction or paravalvular leak during follow-ups. Post-procedural pulmonary artery diastolic pressure increased from 5.8±3.1 mmHg to 11.3±2.5 mmHg. In the 3-month and 1-year follow-up, the right ventricular end diastolic volume index reduced from the baseline 181.6±29.0 ml/m2 to 143.7±29.7ml/m2 and 123.4±31.2 ml/m2, and the trans-pulmonary valve gradient decreased from 25.6±22.2mmHg to 10.64±3.54mmHg and 11.16±3.0 mmHg, respectively. The 6-minute walk distance increased from 416.6±97.9m to 455.9±64.6m and 467.8±61.2m, respectively. Conclusion: This clinical trial revealed favorable outcomes for the safety, efficacy and feasibility of the Med-Zenith PT-Valve in the treatment of severe PR with significantly enlarged RVOT.